Between the Dockyard and the Deep Blue Sea: Retention and Personnel Economics in the Royal Navy - Darrell J. Glaser; Ahmed S. Rahman (Institute of Labor Economics (IZA), 2021)
This paper tackles some issues in personnel economics using the career profiles of British naval officers during the late 19th and early 20th centuries. We ask how promotions, payouts, positions, and peers affect worker retention. Random variation in task assignments and job promotions allows us to explore factors that affect retention of personnel. We develop a number of key insights. Firm-specific human capital accumulation bolsters retention, while technological changes can undo some of this effect. Other challenges to worker retention include lack of promotion opportunities, and "exit contagion" from exits of former peers. Modernizing organizations may need to enhance promotion opportunities and reorganize certain tasks, or else face loss of skilled personnel.
Keywords: J6; J45; J62; N31; 330; personnel economics; human capital; job mobility; promotion tournaments; technological change; military personnel; naval history; peer effects